Is the Concept of Delirious Mania Valid in the Elderly? A Case Report and a Review of the Literature - Maldeniya, Pramudith M.; Vasudev, Akshya (Case Reports in Psychiatry, 2013)
Delirious mania has been well recognized in the published literature and in the clinic. Over the years there has been refinement of understanding of its clinical features, course, and treatment. The literature suggests that delirious mania should be considered in individuals who present with a constellation of sudden onset delirium, mania, and psychosis. However, delirious mania is not recognized under a formal classification system nor are there any formal guidelines for its treatment. We, as such, question if the concept of delirious mania in the elderly is valid. We present a case of an elderly man with marked features of delirium with minimal manic or psychotic features who had a previous diagnosis of bipolar I disorder. On thorough clinical assessments no identifiable cause of his delirium was found. We therefore considered his presentation to be more likely due to delirious mania. Electroconvulsive therapy was considered and offered to which he responded very well. We invite the reader to consider whether delirious mania is a valid concept in the elderly, where features of delirium may be more prominent than manic or psychotic features.